2019
DOI: 10.1038/s41598-019-41595-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated tumour budding quantification by machine learning augments TNM staging in muscle-invasive bladder cancer prognosis

Abstract: Tumour budding has been described as an independent prognostic feature in several tumour types. We report for the first time the relationship between tumour budding and survival evaluated in patients with muscle invasive bladder cancer. A machine learning-based methodology was applied to accurately quantify tumour buds across immunofluorescence labelled whole slide images from 100 muscle invasive bladder cancer patients. Furthermore, tumour budding was found to be correlated to TNM (p = 0.00089) and pT (p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…In particular, we found that high content of TBs in the invasive frontin, frontout, and tumour core as well as low number of CD68 + cells and high PD-L1 expression in the invasive frontout are indicators of bad prognosis. This supports previous findings in the literature [33,36,66,53]. High density of CD8 + , CD3 + , and CD68 + cells in the invasive frontin, frontout, and tumour core was associated with good prognosis by our models, as similarly reported in other studies [23,67].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In particular, we found that high content of TBs in the invasive frontin, frontout, and tumour core as well as low number of CD68 + cells and high PD-L1 expression in the invasive frontout are indicators of bad prognosis. This supports previous findings in the literature [33,36,66,53]. High density of CD8 + , CD3 + , and CD68 + cells in the invasive frontin, frontout, and tumour core was associated with good prognosis by our models, as similarly reported in other studies [23,67].…”
Section: Discussionsupporting
confidence: 93%
“…For the quantification of tumours buds, segmentation of the epithelial cells was required. The CNN-RF methodology described by Brieu et al [71] and extended in [36] was adopted. Briefly, a convolutional neural network (CNN) was trained on an annotated data set of epithelium and non-epithelium IF images.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations